Efficacy and safety of rituximab in autoimmune pancreatitis type 1: our experiences and systematic review of the literature. (2nd November 2021) - Nikolic, Sara; Panic, Nikola; Hintikka, Elina Sofia; Dani, Lara; Rutkowski, Wiktor; Hedström, Aleksandra; Steiner, Corinna; Löhr, J.-Matthias; Vujasinovic, Miroslav
Abstract: Introduction: Autoimmune pancreatitis (AIP) is a special form of pancreatitis that responds well to glucocorticoid (GC) treatment. Relapses of AIP are common. The anti-CD20 antibody rituximab (RTX) has shown promising results in GC refractory cases, but long-term data are scarce. The study aims to determine the clinical and imaging response to RTX and summarize the existing data on RTX therapy in patients with AIP type 1 in the literature. Patients and methods: Retrospective analysis of electronic medical records was conducted. Additionally, we conducted a systematic review of the literature concerning RTX use in AIP type 1. Results: Twelve (11.7%) of 103 patients with AIP type 1 were treated with RTX during the study period: eight (66.7%) achieved complete and four (33.3%) partial remission. RTX was discontinued in one patient who developed fever and reactivation of latent tuberculosis. None of the remaining 11 patients relapsed during a median follow-up of 17 months. No significant differences were detected in baseline clinical characteristics or history of relapse between the patients who obtained complete and partial remission. Altogether, eight studies with 110 AIP type-1 patients treated with RTX were analyzed. Adverse effects ranged from 11–43% and the relapse-free period during follow-up (range 2–173 months) ranged from 38–94%. Conclusions: Our results confirm that RTX is efficacious in the treatment of AIP type 1 by inducing remission and preventing relapse. In addition, there are few adverse effects of the treatment.